An Optimized Pathway for the Differential Diagnosis of ACTH-Dependent Cushing’s Syndrome Based on Low-Dose Dexamethasone Suppression Test - Chen, Kang; Chen, Shi; Lu, Lin; Zhu, Huijuan; Zhang, Xiaobo; Tong, Anli; Pan, Hui; Wang, Renzhi; Lu, Zhaolin (Frontiers in Endocrinology, 2021)
Context: Traditionally, low-dose dexamethasone suppression test (LDDST) was used to confirm the diagnosis of Cushing’s syndrome (CS), and high-dose dexamethasone suppression test (HDDST) was used to differentiate Cushing’s disease (CD) and ectopic adrenocorticotropin (ACTH) syndrome (EAS), but some studies suggested that HDDST might be replaced by LDDST. For the differential diagnosis of CS, dexamethasone suppression test was usually combined with other tests such as bilateral petrosal sinus sampling (BIPSS) and pituitary magnetic resonance imaging, but the optimal pathway to incorporate these tests is still controversial. Objectives: To develop an optimized pathway for the differential diagnosis of CD and EAS based on LDDST. Design and setting: Single-center retrospective study (2011-2019). Patients: 269 CD and 29 EAS patients with pathological diagnosis who underwent consecutive low-dose and high dose DST. Results: For the differential diagnosis of CD and EAS, the area under curve (AUC) of LDDST using urine free cortisol (0.881) was higher than that using serum cortisol (0.685) (p<0.001) in head-to-head comparison among a subgroup of 108 CD and 10 EAS. The AUC of LDDST (0.883) was higher than that of HDDST (0.834) among all the included patients. With the cutoff of <26%, the sensitivity and specificity of LDDST were 39.4% and 100%. We designed a new pathway in which BIPSS was only reserved for those patients with unsuppressed LDDST, yielding an overall sensitivity of 96.2% and specificity of 93.3%. Conclusion: LDDST had similar value to HDDST in differentiating CD and EAS using the specific cutoff. The pathway that combined LDDST, pituitary MRI and BIPSS could differentiate CD and EAS accurately.